2012
DOI: 10.1002/jcla.21484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumatic Tube Delivery System Rate and Distance on Hemolysis of Blood Specimens

Abstract: The rate of hemolysis in PTS transported samples, dependent on PTS length and rate, may seriously affect routine tests of non-centrifuged samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…The system currently installed at the SQUH runs at the optimum transportation rate recommended to avoid the risk of hemolysis [10] and is supported by an auto-unloading system that decreases the risk of sample damage upon arrival to its destination. We have undertaken this study to confirm that Few studies have investigated the effects of a PTS on hematology parameters [1,2,8,12], including these that looked at the ADVIA 2120 [2], Coulter Gen-S [1], and Sysmex XE-2100 systems [13]. One study examined few CBC parameters, but importantly showed that the rate and distance of transportation do not affect CBC results [8].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The system currently installed at the SQUH runs at the optimum transportation rate recommended to avoid the risk of hemolysis [10] and is supported by an auto-unloading system that decreases the risk of sample damage upon arrival to its destination. We have undertaken this study to confirm that Few studies have investigated the effects of a PTS on hematology parameters [1,2,8,12], including these that looked at the ADVIA 2120 [2], Coulter Gen-S [1], and Sysmex XE-2100 systems [13]. One study examined few CBC parameters, but importantly showed that the rate and distance of transportation do not affect CBC results [8].…”
Section: Discussionmentioning
confidence: 81%
“…Few studies have investigated the effects of a PTS on hematology parameters , including these that looked at the ADVIA 2120 , Coulter Gen‐S , and Sysmex XE‐2100 systems . One study examined few CBC parameters, but importantly showed that the rate and distance of transportation do not affect CBC results . A recent study showed no statistical differences for routine hematology testing, erythrocyte sedimentation rate, and reticulocyte count between the PTS and CO method .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristics (e.g., delivery route, velocity) appear to affect sample pressures during transport, which might influence hemolysis rates. Variables that have been shown to cause cell deterioration and increase hemolysis include rapid accelerations and decelerations,17,18 increased length of travel, and high speeds 13,18. Other variables that reduce hemolysis during transport include the use of gel tubes,19 properly filled tubes,16 and padded inserts within the canisters 12…”
Section: Discussionmentioning
confidence: 99%
“…However, this transport method may affect the quality of the samples (pre-analytical step), and thus may have an impact on laboratory results. This mostly depends on PTS technical characteristics, such as length and strong acceleration/deceleration processes (4,5).…”
Section: Introductionmentioning
confidence: 99%